2019
DOI: 10.1117/1.jmi.6.2.024002
|View full text |Cite
|
Sign up to set email alerts
|

Boundary determination of foot ulcer images by applying the associative hierarchical random field framework

Abstract: As traditional visual-examination-based methods provide neither reliable nor consistent wound assessment, several computer-based approaches for quantitative wound image analysis have been proposed in recent years. However, these methods require either some level of human interaction for proper image processing or that images be captured under controlled conditions. However, to become a practical tool of diabetic patients for wound management, the wound image algorithm needs to be able to correctly locate and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Thirty-five full text articles were assessed for eligibility for the study and 17 articles were included in the final analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The entire process of systematic review is reported in accordance to the PRISMA guidelines and flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-five full text articles were assessed for eligibility for the study and 17 articles were included in the final analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The entire process of systematic review is reported in accordance to the PRISMA guidelines and flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…There are five main categories of wound assessment or monitoring techniques or methods: (a) computer applications or hand-held devices (n = 5), 18,19,22,26,27 (b) mobile applications (n = 2), 15,17 (c) optical imaging (n = 2), 13,21 (d) spectroscopy or hyperspectral imaging (n = 4), 20,[23][24][25] and (e) artificial intelligence (n = 4). 11,12,14,16 Uses of wound assessment or monitoring methods were classified into: (a) wound assessment or monitoring and (b) data capturing and storage of information. Sixteen studies reported on wound assessment or monitoring [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27 ; one study reported on data capturing and storage of information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations